Public Space in Transition Co-production and Co-management of Privately Owned Public Space in Seoul and Berlin - Lee, Dahae (Urban Studies, 2022)
Teheran-ro in Seoul and Mediaspree area in Berlin are pristine examples for public spaces with a history of rapid change in the context of broader political and economic transitions. Dahae Lee shows that in such a transitional context, the public sector alone is incapable to provide and manage public space. Hence, it engages private sector entities in the form of privately owned public space/s (POPS). By analysing the planning instruments used for POPS in both cases, their uniqueness as well as strengths and weaknesses are revealed. Based on the results this study offers a number of policy recommendations for cities that encounter similar problems.